2018
DOI: 10.14429/djlit.38.5.13188
|View full text |Cite
|
Sign up to set email alerts
|

Research Contributions of CCS Haryana Agricultural University, Hisar : A Bibliometric Analysis

Abstract: CCS Haryana Agricultural University (CCSHAU) is among the top ten agricultural universities of India according to ICAR ranking 2016-17. The present study has been undertaken to find out the publication trends in this university during 2001-2015. The study mainly focusses on year-wise research output, major subject categories, national and international collaborations, top journals for publication, most prolific authors, keywords, authorship pattern, citations pattern and highly cited paper of CCSHAU. The 15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These findings are supported by prior studies, in line with the notion that the most influential documents and authors are from developed nations (Parmar et al ., 2020; Akintunde et al., 2021; Ganaie and Wani, 2021; Maalouf et al. , 2021; Sweileh, 2021; Siwach and Parmar, 2018). The same pattern was found in institute affiliations, the most influential and impactful affiliations were from reputed institutions ( like the University of Toronto, and Kings College London) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by prior studies, in line with the notion that the most influential documents and authors are from developed nations (Parmar et al ., 2020; Akintunde et al., 2021; Ganaie and Wani, 2021; Maalouf et al. , 2021; Sweileh, 2021; Siwach and Parmar, 2018). The same pattern was found in institute affiliations, the most influential and impactful affiliations were from reputed institutions ( like the University of Toronto, and Kings College London) .…”
Section: Discussionmentioning
confidence: 99%
“…They analysed 2361 documents using multiple variables, focusing on their development, citation quality, subject-wise contribution and effect of prominent researchers, and contribution to the most prolific journals. Siwach and Parmar [3] utilised Scopus to study the research of Chaudhary Charan Singh Haryana Agricultural University's faculty and researchers. They surveyed 2649 publications with 15282 citations, averaging 5.77 per paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Siwach and Parmar, 3 studied the research trends at Haryana Agricultural University. They collected citation data from Scopus database from 2001 to 2015 and observed that nearly half of the articles were published in ten sources, and Annals of Biology was the most preferred journal.…”
Section: Literature Reviewmentioning
confidence: 99%